VISCO-ELASTIC PROPERTIES OF SOFT RELINING MATERIALS - REVIEW - Ilian Hristov; Diyan Slavchev; Stefan Zlatev; Svetlin Alexandrov (Peytchinski Publishing, 2017)
Despite the achievements of modern dentistry in fields of implantology and CAD-CAM technologies, the challenges associated with edentulous patients, treatment are still remaining. Difficulties are getting even greater, when it is a matter of highly atrophied alveolar ridges, covered with very thin mucosa, people suffering from xerostomia, exostosis, very well developed torus palatinus or tuberae maxillae. Problems of the patients with removable dentures usually are poor adhesion and stability, pain, wounds, difficult adaptation with the new dentures, etc. At this moment there are only two possibilities to help these people. The first one is the use of implants; the second one is to use soft relining materials. There are some obstacles that reduce the use of implants in all patients, because of medical, anatomical, psychological and financial concerns. While in the second option the contraindications are quite less.